A reversible fluorescent-colorimetric chemosensor based on a novel Schiff base for visual detection of CO32− in aqueous solution. Issue 76 (29th July 2016) - Ghorai, Anupam; Mondal, Jahangir; Chandra, Rukmani; Patra, Goutam K.
Abstract : A novel Schiff base receptorL has been fabricated for fluorescent-colorimetric detection of CO3 2− in aqueous media.L shows an excellent selectivity, rapid response and reversibility and its sensitivity for CO3 2− is the lowest ever found (96 nM). Abstract : A reversible fluorescent colorimetric chemosensor for rapid detection of carbonate ion has been developed based on a novel bis-Schiff base. The chemosensorL employed here is easy to synthesize, eco-friendly and cost effective. It exhibits excellent selectivity and sensitivity towards carbonate ion by changes in both the absorption and fluorescence intensity. The anion recognition occurs indirectly through coordination of a counter metal ion to the Schiff base ligand exhibiting a colour change from colourless to yellow. Microstructural features ofL andL + M + have been investigated by SEM images. The sensitivity of the absorbance based assay (96 nM) for carbonate ion is the lowest ever reported in the literature. The chemosensorL providing rapid response time with sufficiently low detection limit may be useful as a valuable practical sensor for environmental analyses of carbonate ion.